Influence of age, gender, and willingness to adopt former foodstuffs on the perception of Italian farm animal veterinarians - Diaz Vicuna, Elena; Srikanthithasan, Karthika; Odore, Rosangela; Massaglia, Stefano; Merlino, Valentina Maria; Giorgino, Andrea; Ozella, Laura; Schiavone, Achille; Massacci, Francesca Romana; Mota-Gutierrez, Jatziri; Forte, Claudio (Frontiers in Veterinary Science, 2024)
Veterinarians play an essential role in improving animal care, as they are often viewed as trusted advisors, particularly in relation to disease control and management; however, little is known about veterinarians' perceptions and attitudes towards alternative feeds. The aim of this study was to investigate the influence of age, gender, and willingness to adopt on the attitudes of livestock veterinarians towards the use of alternative feeds in farm animals. A total of 136 active veterinarians completed the online survey, which was distributed through the main veterinary associations in Italy. The questionnaire contained items on dietary recommendation, awareness, benefit and safety perceptions, and a willingness to adopt former foodstuffs (FFs), complemented with sociodemographic questions. Results showed that almost 90% of the population reported a willingness to adopt FFs as feed. Men and women did not share the same perceptions of the nutritional composition of FFs, while the importance of product availability was found to be a key factor driving the age difference. Participants willing to adopt FFs as feed linked positive attitudes to attributes such as digestibility, energy intake, and positive social implications. Our findings provide a basic background on the current use of the FFs in Italy and suggest the need for the development of educational programs and marketing strategies to enhance the acceptability of FFs in farm animals to ultimately promote the transition towards more sustainable animal production. This study has certain limitations, including the limited number of recorded responses and reliance on national estimates. Future research is needed to investigate the perceptions of farmers and animal nutritionist from different countries. This could provide a more detailed picture of the current situation in Europe about the potential of using FFs in farm animals' feed, thus further contributing towards a greener and safer livestock production sector.